Aplikasi Teori Belajar Humanis Dalam Pendidikan Agama Kristen - Jemima Maria Shalom; Roce Marsaulina (JURNAL LUXNOS, 2021)
Abstract: Humanistic Education Theory is humanizing humans. In its development, the model of Christian religious education must be humanistic that can be applied to all groups or individuals in accordance with heterogeneous social conditions, which are not only focused on formal religious education. How is the diversity and pattern of religious education carried out in accordance with the socio-psychology of students so that it is effective and on target. The method used in this writing is a qualitative method with literary studies. The application of humanistic theory refers more to the spirit or spirit during the learning process which colors the method applied. The teacher's role in humanistic learning is to become a facilitator for students. In this case, the teacher's role is very dominant in influencing all sides of students' lives because the teacher is considered a role model, role model and barometer in deciding and instilling all forms of positive attitudes to shape the character of their students. In this case we are taught to support each other to make our neighbors perfect like Christ. One of the principles of humanistic learning theory is that humans have the ability to learn naturally. That is, a person naturally has curiosity and a deep desire to explore the world.           Abstrak: Teori pendidikan humanistik bertujuan untuk memanusiakan manusia. Pendidikan agama Kristen harus humanistik dalam proses perkembangannya, sehingga dapat diterapkan pada semua kelompok atau individu dalam berbagai kondisi sosial, dan tidak terbatas pada pendidikan agama formal. Bagaimana melaksanakan keragaman dan modus pendidikan agama menurut psikologi sosial peserta didik agar efektif dan tepat sasaran. Metode yang digunakan dalam penulisan ini adalah dengan kualitatif kajian ilmiah literatur. Pengoperasian proposisi humanistik mengacu pada semangat atau spirit dalam proses literasi yang mewarnai gaya-gaya yang diterapkan. Bagian dari preceptor dalam literasi humanistik adalah sebagai fasilitator bagi peserta didik. Dalam hal ini peran guru sangat dominan pengaruhnya di semua sisi kehidupan siswa karena guru dianggap sebagai bagian model, bagian model dan tanda dalam menentukan dan membiakkan segala bentuk sikap positif untuk membentuk karakter peserta didik. Dalam hal ini kita diajari untuk saling mendukung untuk menyempurnakan satu sama lain sebagai Kristus. Salah satu prinsip proposisi literasi humanistik adalah bahwa manusia memiliki kemampuan untuk belajar secara alami. Artinya, seseorang secara alami memiliki rasa ingin tahu yang mendalam dan keinginan untuk menjelajahi dunianya.